Event Management Alur Agency in the Implementation of the Exhibition Painting "The Art for Sustainable Living" at Greenhost Boutique Hotel - Kurniyadi, Liana Astrid Jayanti; Setyansih, Rila; Saputri, Dhea Octavia (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
The Art for Sustainable Living is an exhibition theme aimed at raising awareness about sustainability through visual art, representing a sustainable concept practiced by Greenhost Boutique Hotel. The research titled "Event Management by Alur Agency in Executing the Art for Sustainable Living Painting Exhibition at Greenhost Boutique Hotel" examines how Alur Agency, as the organizer, implemented event management stages. The event management by Alur Agency consisted of five stages: research, event design, event planning, event execution, and evaluation. Each stage was analyzed to understand the processes and challenges faced in organizing this exhibition. The research findings indicate that the painting exhibition successfully achieved its primary goal in communication by enhancing public awareness of sustainability issues through visual art. Involving 25 local artists and supported by Greenhost Boutique Hotel and other sponsors, this collaboration created a meaningful event with significant positive impact. This success highlights the importance of effective communication strategies in promoting sustainability values to the broader community.